MULTIPLIER EFFECT PERTANIAN NANAS (Ananas Comosus) TERHADAP PENYERAPAN TENAGA KERJA DAN PENDAPATANMASYARAKAT DI DESA KUALU NANAS, KECAMATAN TAMBANG, KABUPATEN KAMPAR, PROVINSI RIAU - Ridho Al Maghribi; yurni suasti; ratna willis (JURNAL BUANA, 2017)
The purpose of this research is to know the Multiplier Effect of pineapple agriculture in Kualu Nanas village towards the absorption of manpower and community income.This research was conducted in the village of Kualu Nanas, Tambang Subdistrict, Kampa Regency, Riau Province. This research is descriptive quantitative. The population and sample of this research are pineapple farmer in Kampung Riau Village, with 4 sample by looking at seller and industry by using percentage method and using formula to measure multiplier effect.This research found: (1) Multiplier Effect of pineapple agriculture on the absorption of labor affecting service sector, industry and pineapple trader, the value of Multiplier Effect is 1,195. This value shows every addition of one unit of labor base sector (pineapple agriculture) it will result in the addition of non-base sector employment as much as 0.195 times. If the increase of manpower as many as 10 people in the pineapple agriculture sector (base) it will create the opening of employment as much as 2 people in the non-base sector. (2) Multiplier Effect of pineapple agriculture on revenues affects the pineapple industry and trade with a grade of 3.04. This shows that every increase of one unit of pineapple agriculture sector (base) will result in an increase in non-base sector by 2.04 times. If the income increase is Rp.1000. In the base sector it will increase the revenue of Rp. 2.040. In the non-base sector. From the above results with the existence of pineapple agriculture will cause Value added or added value for other sectors.